Identification of Planococcus ficus and Planococcus citri (Hemiptera: Pseudococcidae) by PCR-RFLP of COI gene - Cavalieri, Vincenzo; Mazzeo, Gaetana; Garzia, Giovanna Tropea; Buonocore, Emanuele; Russo, Agatino (Zootaxa, 2008)
The vine mealybug, Planococcus ficus (Signoret), and the citrus mealybug, Planococcus citri (Risso), are currently the most economically important pseudococcids in vineyards in Italy (Dalla Montà et al., 2001). Pl. ficus is also considered to be a key pest in many other countries (Ben-Dov, 1994). The two species cause severe damage to the host plant, and significantly reduce the crop due to the production of honeydew, which allows the growth of sooty molds, and to their potential as virus vectors. The vine mealybug, in particular, is known to transmit grapevine leafroll and corky-bark diseases (Engelbrecht & Kasdorf, 1990; Tanne et al., 1989).